A materialidade da morte no período Ford (1927-1958): memória e patrimônio nos cemitérios de Fordlândia e Belterra, Pará, Brasil - Besen, Ádrea Gizelle Morais Costa (2023)
The present study found in the funerary material culture of the cemeteries of Fordlândia and Belterra founded during the Ford Administration in the Amazon, a universe of historical contexts that would fill some gaps about living and dying during the Ford period in the Tapajós Valley. The Ford project in the Amazon was implemented in the late 1920s, by the industrialist Henry Ford, from the concession of land by the State of Pará in favor of the Ford Industrial Company of Brazil. The were located on the right bank of the Tapajós River and comprised an area known as Boa Vista village, in themunicipality of Aveiro later called Fordlândia. The studies consisted of the identification and analysis of the funerary material culture present in the historical cemeteries of Fordlândia and Belterra, precisely in the remains present in the burials carried out between 1928 and 1958. It was also observed how the cultural and symbolic memory present in the tombstones of the graves are represented and their spatial location in the cemetery. The research was carried out from the bibliographic study of historical sources, and technical reports that comprises the Ford period in the Amazon, from studies of Historical Archaeology and Funerary Archaeology. Data on the cemiterial context were obtained through on-site observation and inventory of the graves and cataloguing of their main characteristics. With the systematization of the data, it was possible to identify an apex in the burials between the years 1929 and 1934 in the cemetery of Fordlândia mainly of adult individuals, and a high number of burials of non-adult individuals during the 1940s and 1950s in the cemetery of Belterra. The data also indicate that the deaths of these individuals occurred in the period in which the spread of infectious diseases had a higher incidence in the Tapajós region.